Voiles racialisés : la femme musulmane dans les imaginaires occidentaux - Al-Saji, Alia (Les ateliers de l'éthique, 2008)
Cet article étudie deux contextes français dans lesquels les voiles musulmans sont devenus hypervisibles : le débat public qui a mené à la loi française de 2004 interdisant les signes religieux ostensibles dans les écoles publiques, et le projet colonial français de dévoiler les femmes algériennes. Je montre comment le concept de « l’oppression de genre » s’est naturalisé au voile musulman d’une telle manière qu’il justifie les normes de féminités occidentales et cache le mécanisme par lequel les femmes musulmanes sont racialisées. C’est ainsi que le voile devient le point de mire d’un racisme culturel qui se présente comme libérant les femmes musulmanes, un racisme qui semble poser un dilemme au féminisme
Keywords: approches et analyses; corps; cours; discipline; droits des femmes*; europe; fem3400; femmes* musulmanes; france; histoire et politique; phi4336; philosophie; premier cycle; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques

Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis